The Influence of Virtual Labs on the Students’ Learning Outcomes and Scientific Attitudes at Physics Education Study Program Flores University - Ilyas Ilyas; An Nisaa Al Mu’min Liu; Hamsah Doa (Universitas Muhammadiyah Makassar, 2020)
This study aims to determine learning outcomes and the scientific attitudes of students at physics education study programs using virtual lab. This type of research is quantitative research. It uses descriptive statistical analysis and inferential stattistics to illustrate data learning outcomes and the scientific attitudes of students at physics education study Universitas Flores using the virtual lab. Data collection techniques used in this study were test for learning outcomes and observatory techniques for the scientific attitude. From the results of descriptive analysis for learning outcomes, it shows that the average is 75,05 in the enough category. The results of inferential statistics show t count is 2,770, sig(2-tailed) 0,011. Because the sig(2-tailed) value of 0,011 is smaller than 0,05, thus it can be concluded that use of the virtual lab influences the learning outcomes. For the scientific attitudes it shows that the average is 76,14 in the enough category. The results of inferential statistics show t count is 3,875, sig(2-tailed) 0,001. Because the sig(2-tailed) value of 0,001 is smaller than 0,05, thus it can be concluded that use of the virtual lab influences the scientific attitudes of students at physics education study Universitas Flores.Keywords: Virtual Lab, Learning Outcomes, Scientific AttitudePenelitian ini bertujuan untuk mengetahui hasil belajar dan sikap ilmiah mahasiswa program studi pendidikan fisika Universitas Flores dengan menggunakan virtual laboratorium. Jenis penelitian ini adalah penelitian kuantitatif , dengan analisis statistik deskfiptif dan statistik inferensial untuk menggambarkan hasil belajar dan sikap ilmiah mahasiswa program studi pendidikan fisika Universitas Flores menggunakan Virtual Laboratorium. Instrumen yang digunakan dalam penelitian ini adalah instrumen tes untuk mengukur hasil belajar serta lembar observasi untuk mengukur sikap ilmiah mahasiswa program studi pendidikan fisika. Dari hasil analisis deskriptif untuk hasil belajar menunjukkan bahwa rata-rata hasil belajar mahasiswa adalah 75,05 dalam kategori cukup, sedangkan hasil statistik inferensial menunjukkan nilai t hitung 2,770, sig(2-tailed) 0,011. Karena nilai sig(2-tailed) 0,011 lebih kecil dari 0,05 hal ini menunjukkan bahwa penggunaan virtual laboratorium berpengaruh terhadap hasil belajar fisika mahasiswa program studi pendidikan fisika Universitas Flores. Untuk sikap ilmiah berdasarkan analisis deskriptif menunjukkan bahwa rata-rata 76,14 dalam kategori cukup, sedangkan hasil statistik inferensial menunjukkan nilai t hitung 3,875, sig(2-tailed) 0,001. Karena nilai sig(2-tailed) 0,001 lebih kecil dari 0,05 hal ini menunjukkan bahwa penggunaan virtual lab berpengaruh terhadap sikap ilmiah mahasiswa program studi pendidikan fisika Universitas Flores.Kata kunci: Virtual Laboratorium, Hasil Belajar, Sikap Ilmiah